Elevated serum levels of aminotransferases in relation to unhealthy foods intake: Tehran lipid and glucose study - Parvin Mirmiran (BMC Endocrine Disorders, 2019)
Abstract Background Abnormal levels of liver enzymes, particularly aminotransferases, are prognostic features of non-alcoholic fatty liver disease (NAFLD). Considering the important role of dietary intakes in development of NAFLD, we aimed to determine possible association of unhealthy foods (fast foods, soft drinks, sweet and salty snacks) consumption with elevated levels of aminotransferases. Methods This cross-sectional study was conducted within the framework of sixth phase of the Tehran Lipid and Glucose Study (2014–2017), on 187 adult men and 249 adult women (19–70 y). Usual intakes of unhealthy foods (kcal/week) were measured using a validated semi-quantitative 147-items food frequency questionnaire. Serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) were measured. Multivariable logistic regression models were used to estimate the odds of elevated aminotransferases in each tertile of energy-dense unhealthy foods. Results Mean age of participants was 44.44 ± 15.09 years, 43% of participants were men. Higher consumption of fast foods (> 11.39% kcal/week) was associated with elevated ALT to AST ratio (OR: 3.27; 95% CI: 1.90–5.63) and elevated ALT (OR: 2.74; 95% CI: 1.57–4.76). Also, each 1 SD increased energy intakes from fast foods was related to increased chance of having elevated ALT and ALT to AST ratio by 35% (OR: 1.35; 95% CI: 1.08–1.68, OR: 1.35; 95% CI: 1.10–1.66, respectively). There was no significant association between consumption of soft drinks, sweet or salty snacks and elevated aminotransferases. Conclusions Higher intakes of energy from fast foods seems to be associated with an elevated serum levels of ALT and ALT to AST ratio, as indicators of development of NAFLD.